Development of Pop-Up Books Based Microsoft Powerpoint to Improve Critical Thinking Skills in Elementary School - Virli Almalia; Bagas Kurnianto (Jurnal Penelitian Pendidikan, 2026)
This research and development was motivated by the low critical thinking skills of students. The purpose of this study was to improve the critical thinking skills of fifth-grade students at Sidayu Public Elementary School. In this study, the researcher used a Research & Development (R&D) approach, which consists of the following stages: needs analysis, product design planning, product development, product validation, and field testing of the product. The feasibility of the product was obtained from expert validation assessments, while the practicality of the learning media was obtained based on the responses of teachers and students. The effectiveness of the media was measured by comparing student learning outcomes before and after using the learning media. The results showed that the Microsoft PowerPoint-based Digital Pop-Up Book learning media obtained very feasible results, analyzed from the aspects of design, material suitability, and practicality in its use. Based on the responses of teachers and students, the Microsoft PowerPoint-based Digital Pop Up Book learning media is practical and easy to use. In addition, the results of the study indicate that there are significant.increase in students' critical thinking skills. Thus, the learning media developed in this study is feasible to be used as an effort to improve students' critical thinking skills in elementary schools.